2017
DOI: 10.3892/ol.2017.7682
|View full text |Cite
|
Sign up to set email alerts
|

Over-activated PD-1/PD-L1 axis facilitates the chemoresistance of diffuse large B-cell lymphoma cells to the CHOP regimen

Abstract: Abstract.Interaction between the programmed cell death ligand 1 (PD-L1) and programmed cell death 1 (PD-1) contributes to tumor cell resistance to chemotherapeutic agents. PD-L1 is expressed in the cells of diffuse large B-cell lymphoma (DLBCL), one common type of malignant non-Hodgkin lymphomas. However, little is known about how the PD-1/PD-L1 pathway functions in the pathogenesis of DLBCL. Therefore, the present study investigated whether and how the PD-1/PD-L1 axis is involved in regulating the sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
(30 reference statements)
1
17
1
Order By: Relevance
“…The programmed cell death 1 (PD1)/programmed cell death‐ligand 1 (PD‐L1) axis, which plays an important role both in transplanted organ tolerance and in antitumour immune responses, has been studied in different haematological neoplasms . Nevertheless, its clinical and biological significance in PTLD is largely unknown …”
Section: Introductionmentioning
confidence: 99%
“…The programmed cell death 1 (PD1)/programmed cell death‐ligand 1 (PD‐L1) axis, which plays an important role both in transplanted organ tolerance and in antitumour immune responses, has been studied in different haematological neoplasms . Nevertheless, its clinical and biological significance in PTLD is largely unknown …”
Section: Introductionmentioning
confidence: 99%
“…23 Another possible reason is that chemotherapeutic resistance may arise from positive PD-L1 expression partly, which may link to poor prognosis. 21 These findings suggest that PD-L1 expression may be favorable to discover GDLBCL patients who have a high disease progression risk.…”
Section: Discussionmentioning
confidence: 92%
“…20 Therefore, GDLBCL patients with high PD-L1 expression do not benefit from first-line treatment. 21 In literature reports, tumor cells that express PD-L1 have many mechanisms to escape T-cell immunity. 22 PD-1/PD-L1 pathway induces apoptosis of PD-1 + tumor-associated antigen-specific T cells, which is one of its important mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Data for the regulation of apoptotic susceptibility by PD-L1 derived from a limited number of studies in solid tumor cell lines [45][46][47]. We found that the intrinsic PD-L1 of tumor cells can regulate chemosensitivity, and knockout of PD-L1 can make human and mouse CRC cell lines resist the apoptosis induced by various cytotoxic drugs.…”
Section: Discussionmentioning
confidence: 95%